PENGARUH PENERIMAAN PAJAK, DAN TINGKAT INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Refilio Andika Pratama (2022)
This study aims to examine the effect of tax revenue and inflation rate on economic growth in Indonesia. The variables used in this study are the level of tax revenue, the rate of inflation and also the rate of economic growth in Indonesia. The sample used in this study amounted to 30 samples with a total research data of 90 data originating from 30 years of research multiplied by 3 economic data variables, namely data on the ratio of tax revenues, inflation rates and also GDP. The sample selection technique in this study uses judgment sampling because the sample to be used by the researcher considers the completeness of the available data related to the variables in the study. Testing the hypothesis in this study using multiple linear regression. This study shows that tax revenue has no effect on economic growth in Indonesia. In addition, this study gives the result that the inflation rate variable has a negative effect on the variable of economic growth in Indonesia.